Identification and analysis of differentially expressed long non-coding RNAs of Chinese Holstein cattle responses to heat stress. Issue 1 (2nd January 2020) - Li, Qiuling; Qiao, Jie; Zhang, Zhengfeng; Shang, Xiaolan; Chu, Zhuodong; Fu, Yajuan; Chu, Mingxing
Abstract: The mechanisms that dairy cattle respond to environmental stresses are very complicated. Previous research into the molecular mechanisms of mammalian heat stress has largely focused on the role of protein-coding genes and small non–coding RNAs. Recently, it has become apparent that large numbers of long non-coding RNAs transcribed from mammalian genomes play extensive roles in transcriptional regulation. However, the expression of lncRNAs and their biological functions in heat stress in dairy cattle remain unknown. In this study, we employed a deep RNA sequencing to examine lncRNA expression profiles of heat stressed and non-heat stressed Chinese Holstein cattle. We found that 24, 795 novel and 3763 known lncRNAs were expressed in the bovine mammary gland, of which 174 were differentially expressed in heat stress condition, among them, 156 lncRNAs were up-regulated and 18 were down-regulated. Through Cis role analysis, 16, 474 lncRNAs were transcribed close to protein-coding neighbors. In addition, 11 and 2024 lncRNAs harbored precursors of known and predicted microRNAs, respectively, were annotated in the precursor analysis of miRNAs. Taken together, our findings represent the first systematic investigation of lncRNA expression in heat stressed Chinese Holstein and provide a resource for further research into the molecular mechanisms of lncRNAs function in dairy cattle.